Effect of fullerenes on flame retardancy of polymeric substrates [review] - Gocek, Ikilem; Keskin, Reyhan (Editura Universităţii din Oradea, 2020)
Flame retardancy is a modern challenge especially in living area applications as many flame retardants such as halogenated and brominated chemicals possess health risks. Studies show that fullerenes have potential for flame retardant applications. Flame retardancy property of fullerene included polymers is explained in this paper. Fire hazards have been risks for human beings through all history. In modern era, closed areas such as houses, offices and cars are full of organic and polymeric materials and possess serious fire risks. Organic polymers are widely used in many daily applications due to their mechanical properties and price availability. As organic polymers are flammable naturally, the flame retardancy of polymeric materials is becoming an important issue in living areas. Conventional flame retardant materials have found a large usage; however, they have some drawbacks as need of high level loading and environmental issues. For flame retardancy applications, mainly seven elements are efficient in polymers: chlorine, bromine, aluminum, boron, phosphorus, nitrogen and antimony. Large amounts of conventional flame retardants are needed to ensure flame retardancy requirements. High loading levels of conventional flame retardants cause detrimental decreases in mechanical properties of the hosting polymer and cause transparency loss of the matrix material as well. In conclusion, the effect of Fullerene (C60), as a nanocarbonaceous material, on flame retardancy properties of polymeric materials is explained. Fullerenes not only increase strength properties of polymeric substrates but also can enhance the flame retardancy of polymers. Fullerenes can alter the flammability of polymeric materials, which might find applications in many areas of our daily lives, and result in increased flame retardant properties of polymeric materials including textiles.
Keywords: fabric substrates.; Manufactures; nanocarbonaceous materials; flame retardancy; polymers; TS1-2301; fullerene (c60)